Drug policy developments within the European Union. The destabilizing effects of Dutch and Swedish drug policies - Chatwin, Caroline (The British journal of criminology, 2003)
This paper examines the course of drug control within the European Union (EU). The individual policies of both the liberal Netherlands and the more repressive Sweden are explained in detail, and the effects they have on the EU as a whole are discussed. In order to understand these effects more fully an inspection of recent drug legislation developed in the fight against drugs is undertaken. Current trends relating to the drug problem that can be identified throughout the member states are presented and evaluated with respect to the policies of both the Netherlands and Sweden. A division within the EU centring around the different policy styles of these two nations is discussed and possible solutions to the division are raised. Finally, the positive effects that this battle has resulted in are noted